2018
DOI: 10.1186/s40814-018-0308-2
|View full text |Cite
|
Sign up to set email alerts
|

Walk with Me: a protocol for a pilot RCT of a peer-led walking programme to increase physical activity in inactive older adults

Abstract: BackgroundLevels of physical activity decline with age. Some of the most disadvantaged individuals in society, such as those from lower socio-economic position, are also the most inactive. Increasing physical activity levels, particularly among those most inactive, is a public health priority. Peer-led physical activity interventions may offer a model to increase physical activity in the older adult population. This study aims to test the feasibility of a peer-led, multicomponent physical activity intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…It is possible that males could have differing opinions and experiences of the monitoring device. However, as Tully et al also found in their CBPR walking study [ 30 ], a disproportionate amount of females over males engage in community walking programmes and our research reflects this naturally occurring gender difference in community exercise participation. In addition, some of our participants had previous experiences of using activity monitoring devices; two participants previously used phone apps for step counting and one used her own wearable device.…”
Section: Discussionsupporting
confidence: 72%
“…It is possible that males could have differing opinions and experiences of the monitoring device. However, as Tully et al also found in their CBPR walking study [ 30 ], a disproportionate amount of females over males engage in community walking programmes and our research reflects this naturally occurring gender difference in community exercise participation. In addition, some of our participants had previous experiences of using activity monitoring devices; two participants previously used phone apps for step counting and one used her own wearable device.…”
Section: Discussionsupporting
confidence: 72%
“…Dyads with volunteer buddies worked well, bypassing complex relationship challenges, although matching and developing these dyads required time and careful facilitation. Other walking intervention studies have successfully used volunteer buddies [39], and the option should be pursued more extensively for the next WeWalk study phase.…”
Section: Discussionmentioning
confidence: 99%
“…Development and feasibility studies of a community-based peer-led walking intervention to increase PA in inactive older people40 reflected similar intervention development processes to We Walk. Authors used social-cognitive theory and a socioecological model to develop and include BCTs; however, the final BCTs and intervention structure aligned with We Walk.…”
Section: Discussionmentioning
confidence: 99%